Radial tension in nuclear containment vessels - Weinhold, Samuel F. (My University, 2025)
Delamination in concrete nuclear pressure vessels is an expensive and dangerous phenomenon that has not been adequately studied or understood. The 2009 Crystal River Unit 3 pressure vessel delamination is the most recent and most consequential example of this phenomenon. In this event, the pressure vessel wall delaminated during steam generator replacement. The vessel was unable to be repaired. Unit 3 is currently undergoing the decommissioning process. This research was built on research already conducted by the University of Texas at Austin. Six miniature mortar 90⁰ wall sections were constructed making use of a 3D printer to construct the curved formwork for the specimens. This setup allows for a multitude of variables to be tested more efficiently owing to the small specimen size. This research focused on three variables radius, mortar strength, and the use of steel fibers in mix design. Results showed that delamination is influenced by in-plane shear; a previously understudied mechanism of delamination. Increasing concrete strength and the use of steel fibers give the wall sections greater resistance to delamination and a noticeable increase in toughness. Delamination is a mixed-mode fracture problem related closely to direct tension and in-plane shear. This research shows a factor of 3.75√(f'c) can be conservatively used to estimate direct tensile strength for concrete. Results also showed that limit states for precompression may need to be modified in the ASME Section III Division 2 design code.
Keywords: Radial tension; Delamination; Pressure vessel